Laparoscopic Hartmann's reversal has better clinical outcomes compared to open surgery: An international multicenter cohort study involving 502 patients. Issue 5 (1st September 2022) - Medellin Abueta, Anwar; Senejoa, Nairo Javier; Pedraza Ciro, Mauricio; Fory, Lina; Rivera, Carlos Perez; Jaramillo, Carlos Edmundo Martinez; Barbosa, Lina Maria Mateus; Varela, Heinz Orlando Ibañez; Carrera, Javier A.; Garcia Duperly, Rafael; Sanchez, Luis A; Lozada‐Martinez, Ivan David; et al.
Abstract: Background: Hartmann's procedure (HP) is used in surgical emergencies such as colonic perforation and colonic obstruction. "Temporary" colostomy performed during HP is not always reversed in part due to potential morbidity and mortality associated with reversal. There are several contributing factors for patients requiring a permanent colostomy following HP. Therefore, there is still some discussion about which technique to use. The aim of this study was to evaluate perioperative variables of patients undergoing Hartmann's reversal using a laparoscopic and open approach. Methods: The multicenter retrospective cohort study was done between January 2009 and December 2019 at 14 institutions globally. Patients who underwent Hartmann's reversal laparoscopic (LS) and open (OS) approaches were evaluated and compared. Sociodemographic, preoperative, intraoperative variables, and surgical outcomes were analyzed. The main outcomes evaluated were 30‐day mortality, length of stay, complications, and postoperative outcomes. Results: Five hundred and two patients (264 in the LS and 238 in the OS group) were included. The most prevalent sex was male in 53.7%, the most common indication was complicated diverticular disease in 69.9%, and 85% were American Society of Anesthesiologist (ASA) II‐III. Intraoperative complications were noted in 5.3% and 3.4% in the LS and OS groups, respectively. Small bowel injuries were the most common intraoperative injury in 8.3%, with a higher incidence in the OS group compared with the LS group (12.2% vs. 4.9%, p  < 0.5). Inadvertent injuries were more common in the small bowel (3%) in the LS group. A total of 17.2% in the OS versus 13.3% in the LS group required intensive care unit (ICU) admission ( p  = 0.2). The most frequent postoperative complication was ileus (12.6% in OS vs. 9.8% in LS group, p  = 0.4)). Reintervention was required mainly in the OS group (15.5% vs. 5.3% in LS group, p  < 0.5); mortality rate was 1%. Conclusions: Laparoscopic Hartmann's reversal is safe and feasible, associated with superior clinical outcomes compared with open surgery.